THE IMPACT OF LIQUIDITY RATIO, SOLVENCY, AND PROFITABILITY ON THE FINANCIAL PERFORMANCE OF PT. PANJI ANUGERAH SENTOSA MEDAN DURING 2022-2024 - Muhammad Dimas Alfahri; Toni Hidayat; Rukmini; Muhammad Dani Habra (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study aims to analyze the influence of liquidity, solvability, and profitability on the financial performance of PT. Panji Anugerah Sentosa Medan during the 2022–2024 period. The research employed a quantitative approach using secondary data in the form of financial statements, with a total sampling technique. The analytical methods used include classical assumption tests (normality, multicollinearity, and heteroscedasticity), multiple linear regression, F-test (simultaneous), t-test (partial), and the coefficient of determination (R²). The normality test results indicated that the residuals were normally distributed (Asymp. Sig. = 0.200 > 0.05), the multicollinearity test showed no correlation among the independent variables (VIF < 10), and the heteroscedasticity test confirmed that the model was free from heteroscedasticity issues (Sig. > 0.05). The F-test yielded an F value of 13.203 > F table 2.891 with a significance level of p = 0.000, indicating that liquidity, solvability, and profitability simultaneously have a significant effect on financial performance. Partially, the t-test results showed that liquidity had a significant negative effect on financial performance (|-2.625| > 2.3452 and Sig. = 0.013 < 0.05), profitability had a significant positive effect (3.396 > 2.3452 and Sig. = 0.002 < 0.05), while solvability had no significant effect (0.035 < 2.3452 and Sig. = 0.972 > 0.05). The adjusted coefficient of determination (Adjusted R²) was 0.511, indicating that 51.1% of the variation in financial performance is explained by the three independent variables.